Effect of Corporate Competitive Excellence, Employee Performance and Inventory Information on the Resource Information System (Literature Review) - M. Raka Mahendra (Dinasti International Journal of Management Science, 2023)
Literature Review Articles Effect of Corporate Competitive Excellence, Employee Performance and Inventory Information on The Resource Information System is a scientific article that aims to build a hypothesis of influence research between variables that will be used in subsequent research, within the scope of Management Information Systems. The method of writing this Literature Review article is by the method library research, sourced from online media such as Google Scholar, Mendeley and media online other academics. The results of this article are that: 1) Competitive Excellence Companies influence the Resource Information System; 2) Employee Performance affects the Resource Information System; and 3) Inventory Information affects Resource Information System. Seal from 3 variable exogen this the one influence variable Endogenous Resource Information System there are still many other factors including variables hardware, software, data and networks